Hollywood romantic comedies: a social semiotic analysis of the leading female characters in It happened one night and The proposal - Macedo, Litiane Barbosa (2014)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2014.